Examining the Determinants of the South African Current Account Deficit and its Sustainability - Ncanywa, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Countries that run large current account deficits (CAD) signal negative perceptions to investors as the deficits might not be sustainable. Credit risk posed by currency weakness, credit downgrades and political uncertainties link to increased macroeconomic risks. The paper aims to find, in a first step, the determinants of South Africa’s current account and, in a second step; to examine whether its current deficit is sustainable. To find the determinants of the CAD, an autoregressive distributive lag model (ARDL) is used with quarterly time series data spanning the post-apartheid era [1994-2017]. The ARDL bounds test results indicate that a long run relationship exists between the determinants of the CAD. Factors such as household savings, growth rate have positive significant impacts and net portfolio investments have a negative impact on the South African CAD. Further analyses evaluate, by using scenario analysis including feedback between the stock of debt and flows of income payments, the sustainability of the South African current account deficit. It turns out that the current deficit is not sustainable and that a further real depreciation of the rand is recommended.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Current account deficit; Growth rate; Household savings; Income payments; Net portfolio investment; Sustainable development -- South Africa; Budget deficits --South Africa